Pharmaco-epidemiology of antidepressant exposure in a UK cohort record-linkage study. (April 2019) - Hafferty, Jonathan D; Wigmore, Eleanor M; Howard, David M; Adams, Mark J; Clarke, Toni-Kim; Campbell, Archie I; MacIntyre, Donald J; Nicodemus, Kristin K; Lawrie, Stephen M; Porteous, David J; McIntosh, Andrew M
Objectives: Antidepressants are the most commonly prescribed psychiatric medication but concern has been raised about significant increases in their usage in high income countries. We aimed to quantify antidepressant prevalence, incidence, adherence and predictors of use in the adult population. Methods: The study record-linked administrative prescribing and morbidity data to the Generation Scotland cohort ( N = 11, 052), between 2009 and 2016. Prevalence and incidence of any antidepressant use was determined. Antidepressant adherence was measured using Proportion of Days Covered and Medication Possession Ratio. Time-to-event analysis for incident antidepressant use within 5 years of Generation Scotland: Scottish Family Health Study (GS:SFHS) recruitment was performed to reveal patient-level predictors of use. Results: Almost one-third (28.0%, 95%CI 26.9–29.1) of the adults in our sample were prescribed at least one antidepressant in the 5-year period 2012–2016. There was a 36.2% increase in annual prevalence between 2010 and 2016. Incidence was 2.4(2.1–2.7)% per year. The majority of antidepressant episodes (57.6%) were greater than 9 months duration and adherence was generally high (69.0% with Proportion of Days Covered >80%). Predictors of new antidepressant use included history of affective disorder, being female, physical comorbidities, higher neuroticism scores, and lower cognitive function scores. Conclusions: Antidepressant prevalence is greater than previously reported but incidence remains relatively stable. We found the majority of antidepressant episodes to be of relatively long duration with good estimated adherence. Our study supports the hypothesis that increased long-term use among existing (and returning) users, along with wider ranges of indications for antidepressants, has significantly increased the prevalence of these medications.